Solid‐state reflective displays (SRD) utilizing ultrathin phase‐change materials - Broughton, B; Bandhu, L; Talagrand, C; Garcia-Castillo, S; Yang, M; Bhaskaran, H; Hosseini, P (Wiley, 2017)
Devices based on ultra‐thin‐films of solid‐state phase‐change materials (PCMs) provide an entirely new means of achieving bistable, bright, vividly coloured, switchable reflective surfaces. In this paper, we outline the electro‐optic mechanism underpinning these devices, discuss their unique potential to enable a new class of video capable colour reflective displays, and present for the first time repeatable electrical switching of display‐pixel sized PCM devices between two highly contrasting optical states.